The Fidget Factor and the obesity paradox. How small movements have big impact - Levine, James A. (Frontiers in Sports and Active Living, 2023)
The hypothesis is that the Fidget Factor is the innate neurological pulse that propels humans and other species to move to support their health. Fidgets, previously thought to be spontaneous, are neurologically regulated and highly ordered (non-random). Modern societies being chair-based overwhelm Fidget Factor pulses and consequently inflict chair-based living for transportation, labor, and leisure. Despite impulses firing through the nervous system, people sit because environmental design overwhelms the biology. Urbanization and chair-based societies were designed after the industrial revolution to promote productivity; however, the consequence has been opposite. Crushing the natural urge to move—the Fidget Factor—is a public health calamity. Excess sitting is associated with a myriad of detrimental health consequences and impairs productivity. Fidgeting may reduce all-cause mortality associated with excessive sitting. The Fidget Factor offers hope; data demonstrate that workplaces and schools can be designed to promote activity and free people's Fidget Factors. Evidence shows that people are happier, healthier, wealthier, and more successful if their Fidget Factors are freed.